Identification of a Redox Active Thioquinoxalinol Sulfate Compound Produced by an Anaerobic Methane-Oxidizing Microbial Consortium - White, Robert H. (ACS Omega, 2019)
[Image: see text] The anaerobic oxidation of methane (AOM) mitigates the flux of methane from marine sediments into the water column. AOM is performed by anaerobic methanotrophic archaea (ANME) that reverse the methanogenesis pathway and partner bacteria that utilize the released reducing equivalents for sulfate reduction. Here, we investigated small-molecule extracts from sediment-free thermophilic enrichment cultures of ANME-1 and sulfate-reducing bacteria using ultraperformance liquid chromatography with high-resolution mass spectrometry. During the analysis, we discovered a novel thioquinoxalinol-containing redox molecule as a major component of the chemically derivatized small-molecule pool. This compound contains both a redox active quinoxaline heterocyclic ring and a thiol group. Additionally, the same core structure was identified that contains a sulfate ester on the hydroxyl group, which likely makes the molecule more water soluble. Hydrated versions of both structures were also observed as major compounds in the extracts. On the basis of reactions of model compounds such as quinoxalin-6-ol, the hydrated version appears to be formed from the addition of water to the dehydropyrazine ring followed by an oxidation. These thioquinoxalinol compounds, which represent completely new structures in biochemistry, may be involved in electron transport processes within and/or between ANME-1 and sulfate-reducing bacteria, may serve protective roles by reacting with toxic compounds such as hydrogen sulfide, or may transport sulfate as a sulfate ester into the sulfate-reducing bacteria.